APLIKASI COUPLER UNTUK MENGATASI GANGGUAN TRAFICK DATA ANTARA STO PONTIANAK CENTRUM – STO SIANTAN PT. TELKOM PONTIANAK - ., Herdi Wiryanto (Faculty of Engineering, Universitas Tanjungpura, 2016)
Transmission system fiber optics between STO Pontianak Centum STO Siantan, now already using two lane fiber optics. The first lane be name